Implementation of Kerberos method on DDAS system and search data speedily from extracted Zip data - Gulhane, Suraj; Bodkhe, Sonali (International Journal of Computer Sciences and Engineering, 2025)
Deploying application over the web is increasing day by day. Such deployed application useful for client to store as well as retrieve database to/from particular server. Over the web data stored in distributed manner so flexibility, reliability, scalability and security are important aspects need to be considered while constructed data management system. After analyzing Distributed data aggregation service(DDAS) system which maintain a catalog which is relying on Blobseer it found that it provide a good performance in aspects such as data storage as a Blob (Binary large objects) and fast retrieval of data by data aggregation process. For highly complex analysis and instinctive mining of scientific data, Blobseer act as a repository backend for easy retrieval of data. By using this Kerberos method client will able to done a secure authentication as using this method only authorized clients are able to access distributed database. Kerberos consist of 4 steps i.e. Authentication Key exchange, Ticket granting service Key exchange, Client/Server service exchange and Build secure communication. After that aggregation of data carried out and aggregated data catalog is generated. From that catalog user is able to search a required data and this data in zip file form saved at client side. For zipping purpose Adaptive Huffman method is used (also referred to as Dynamic Huffman method) which is based on Huffman coding. It permits compression as well as decompression of aggregated data.